On a special critical case of stability of a nonautonomous essentially nonlinear system - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We obtain sufficient conditions for the Lyapunov stability of the trivial solution of a nonautonomous essentially nonlinear differential system in a special critical case.